Genetic algorithm for optimal channel assignment for mobile communications - Shanmugasundaram Arunkumaar. (2008)
In this dissertation, we are concerned with the problem of assigning calls in a cellular mobile network to frequency channels in such a way that the interference between calls is minimized, while demands for channels are satisfied. Genetic algorithms are used to solved this problem.